Behavior and social computing : international workshop on behavior and social informatics, BSI 2013, Gold Coast, QLD, Australia, April 14-17, 2013 and International Workshop on Behavior and Social Informatics and Computing, BSIC 2013, Beijing, China, August 3-9, 2013, Revised Selected Papers - Motoda, Hiroshi; Srivastava, Jaideep; Lim, Ee-Peng; King, Irwin; Yu, Philip S.; Nejdl, Wolfgang; Xu, Guandong; Li, Gang; Zhang, Ya (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed proceedings of the International Workshops on Behavior and Social Informatics and Computing, BSIC 2013, held as collocated event of IJCAI 2013, in Beijing, China in August 2013 and the International Workshop on Behavior and Social Informatics, BSI 2013, held as satellite workshop of PAKDD 2013, in Gold Coast, Australia, in April 2013. The 23 papers presented were carefully reviewed and selected from 58 submissions. The papers study a wide range of techniques and methods for behavior/social-oriented analyses including behavioral and social interaction and network, behavioral/social patterns, behavioral/social impacts, the formation of behavioral/social-oriented groups and collective intelligence and behavioral/social intelligence emergence.